(untitled) (مجلة الواحات للبحوث والدراسات, 2022)
الملخص: لعل أكثر الترابطات والأشد أهمية تلك المتواجدة بين مخرجات المنظومة التكوينية ومتطلبات الحياة العملية في الجزائر؛ بحيث يهدف كل منهما وفق المعايير الكمية والكيفية الى تحقيق التنمية في شتى الميادين الاقتصادية والاجتماعية. وفي ظل علاقة تكوين عمل والتوجهات الكبرى التي يعرفها سوق الشغل اليوم وجب على القائمين على هذان القطاعان وضع استراتيجية واضحة المعالم تعمل على خلق الانسجام بينهما، وذلك لتسهيل عملية الإدماج المهني لأكبر عدد ممكن من مخرجات المنظومة التكوين الكلمات المفتاحية: الاستخدامية؛ المخرجات؛ المنظومة التكوينية؛ سوق الشغل. Abstract: Perhaps the most important and most important interconnections are between the outputs of the training system and the requirements of practical life in Algeria. So that each of them aims, according to quantitative and qualitative criteria, to achieve development in various economic and social fields. In light of the relationship of job formation and the major trends in the labor market today, those in charge of these two sectors must develop a clear-cut strategy that works to create harmony between them, in order to facilitate the process of professional integration of the largest possible number of the outputs of the training system.; Keyword: Usability; Outputs; Formative system; The job market.